Sub-ns-pulsed laser cleaning of an archaeological bone from the Sierra de Atapuerca, Spain: a case study - Schiavon, Nicola (2022)
Controlled laser irradiation parameters using recently developed sub-nanosecond pulsed laser technology with emission wavelength in the near Infrared regime (1064 nm) have been assessed on a Pleistocene bone from the archaeological site of Sierra de Atapuerca, Spain. Burst pulse mode was employed to explore contaminant removal efficiency, while at the same time, assessing the degree of damage produced to the underlying original substrate surface. The surface morphology and composition of the deteriorated bone have been characterized, along with the effects of laser irradiation at 1064 nm, using Optical Microscopy (OM), Scanning Electron Microscopy–with Energy Dispersive X-ray Spectrometry (SEM–EDS), and X-ray Photoelectron Spectroscopy (XPS). The most effective laser cleaning parameters in burst mode have been identified in order to optimize the emission parameters of the laser, thus localizing its interaction within the outermost layers of contaminants and degradation products, avoiding damage to the underlying original bone surface. Hence, threshold cleaning and substrate damage values have been determined for this new sub-ns laser, paving the way to safer laser cleaning procedures that may be useful for the effective conservation of bone archaeological artifacts.